2021
DOI: 10.1021/acs.molpharmaceut.1c00653
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal siRNA Nanoparticles for Augmentation of Gemcitabine Efficacy in the Treatment of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma is a deadly disease with limited treatment options due to late diagnosis and resistance to conventional chemotherapy. Among emerging therapeutic targets, the CXCR4 chemokine receptor and polo-like kinase 1 (PLK1) play critical roles in the progression, metastasis, and chemoresistance of pancreatic cancer. Here, we tested the hypothesis that combining CXCR4 inhibition by a polymeric CXCR4 antagonist PAMD-CHOL with PLK1 knockdown by siRNA will enhance the therapeutic effect of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“… Lipid NP RRM2 Mouse Intraperitoneal and Peritumoral siRNA and DOX Panc-1 Reduction in tumour growth, decreased metastasis and DOX dose [ 117 ] 6. Polymer NP PLK 1 Mouse Intraperitoneal siRNA and GEM KPC8060 and S2–013 Greater accumulation in tumours and significant increase in anti-cancer activity [ 118 ] 7. Dendrimer ITCH Mouse Subcutaneous siRNA and GEM Mia-PaCa-2, BxPC3 and Panc-1 Significant gene knockdown and increased chemo sensitivity [ 43 ] 8.…”
Section: A Cocktail Of Aptamer/sirna Mediated Chemotherapy Against Pa...mentioning
confidence: 99%
See 1 more Smart Citation
“… Lipid NP RRM2 Mouse Intraperitoneal and Peritumoral siRNA and DOX Panc-1 Reduction in tumour growth, decreased metastasis and DOX dose [ 117 ] 6. Polymer NP PLK 1 Mouse Intraperitoneal siRNA and GEM KPC8060 and S2–013 Greater accumulation in tumours and significant increase in anti-cancer activity [ 118 ] 7. Dendrimer ITCH Mouse Subcutaneous siRNA and GEM Mia-PaCa-2, BxPC3 and Panc-1 Significant gene knockdown and increased chemo sensitivity [ 43 ] 8.…”
Section: A Cocktail Of Aptamer/sirna Mediated Chemotherapy Against Pa...mentioning
confidence: 99%
“…In vivo profiles of the nanoparticles demonstrated that the combined delivery of PAMD-CHOL-siPLK1-GEM showed increased anti-tumour activity in comparison to a single control. Thus it can be concluded that combinatorial delivery was proved to be beneficial in treating PC [ 118 ].…”
Section: A Cocktail Of Aptamer/sirna Mediated Chemotherapy Against Pa...mentioning
confidence: 99%
“…Nanoparticles can target a wide range of physiological and metabolic characteristics of the targeted tissues, thereby increasing biodistribution and bioavailability of drugs and enhancing their plasma half-life and EPR ( Parhi et al, 2012 ; Poon et al, 2015 ; Gad et al, 2016 ; Liu et al, 2022 ). Recently, the potency of the chemotherapeutic agents for the treatment of PC has been improved through the use of RNA interference (RNAi) technologies, including miRNA and siRNA, which selectively suppress the expression of target genes leading to increased drug efficacy and enhancing anti-cancer activity ( Tang et al, 2021 ). Integrating RNAi with NPs can therefore be extremely effective at treating PC ( Hiss et al, 2007 ; Gurunathan et al, 2018 ).…”
Section: Nano-based Intervention To Overcome Mdr-pc In Pre-clinical A...mentioning
confidence: 99%
“…Thus, CXCR4 and PLK1 targeting may represent an interesting approach to overcome GEM resistance. Tang et al [ 57 ] developed a strategy based on the use of a polymeric molecule able to antagonize CXCR4 and to carry a siRNA against PLK1 (Pol-siPLK1). In vitro, in the pancreatic cancer cells KPC8060, Pol-siPLK1 achieved nearly 48% target knockdown and 68% in another pancreatic cancer cell line named S2-013.…”
Section: Sirnas For the Gi Cancersmentioning
confidence: 99%